Sign Languages : Cambridge Language Surveys - Brentari, Diane (UK : Cambridge University Press, 2010)
Written in a clear, readable style, it is the essential reference for students and scholars working in sign language studies
History and Transmission, Shared crosslinguistic characteristics, Variation and Change.
Keywords: Language And Linguistics